15.1k views
2 votes
I’m not sure how to solve a problem like this and also state the excluded values.

(4n/n+4)-(5n/n-3)

User Gusbro
by
5.6k points

1 Answer

5 votes

After solving, we get the final expression as:
\frac{-n^(2)-32n {} }{(n+4)(n-3)}

Explanation:

Given:


(4n)/(n+4) - (5n)/(n-3)

=
(4n)/(n+4) - (5n)/(n-3)

Now taking L.C.M,

=
(4n(n-3)-5n(n+4))/((n+4)(n-3))

Simplify the equation in numerator,

=
\frac{4n^(2)-12n-5n^2 {-20n} }{(n+4)(n-3)}

= =
\frac{-n^(2)-32n {} }{(n+4)(n-3)}

Thus, this is the required solution:
\frac{-n^(2)-32n {} }{(n+4)(n-3)}

User Siutsin
by
6.3k points